A Clinical Course And Follow Up Of Two Collodion Babies - Jain Chanchal; Chopra Adarsh; Jassal Jasbir Singh; Shoba Prabhat; Gupta Monika (Wolters Kluwer Medknow Publications, 2001)
Two collodion babies were followed clinically. One of the babies expired due to inadequate management while the other child survived due to combined efforts of paediatricians and dermatologists.